Volume 198, January–December 2014 (Genetics, 2014)
Below is a list of individuals who have reviewed manuscripts for GENETICS during the preparation of volumes 196, 197, and 198 (2014). The aim of GENETICS is to communicate significant research. To succeed, we must recognize what is significant, making sure the presentation is accurate, unambiguous, and easily readable. For this, we depend heavily upon our reviewers, who perform this indispensable service without reward. The quality of the journal strongly reflects the quality of their efforts. We apologize to any reviewer whose name has been inadvertently omitted, and we are sincerely grateful to all.